Colonic perforation in percutaneous nephrolithotomy: a case report - Abd Aziz, Mohd Fahmi; Mahno, Noor Ezmas; Che Mohamed, Siti Kamariah; Mohd Zahid, Nazli (Kulliyyah of Medicine, International Islamic University Malaysia, 2018)
We aim to report a rare case of colonic perforation post percutaneous nephrolithotomy (PCNL) and its conservative management. We report a 63-year-old Malay, thalassemia carrier male who underwent an uncomplicated left PCNL for a left renal stone. On second postoperative day, clinically evidence of subcutaneous emphysema. Serial CXR imaging confirmed presence of air under diaphragm. Small colonic perforation was diagnosed which subsequently developed localized collection retroperitoenally. He was successfully treated with non-operative management including intravenous antibiotic, surgical drainage and good nutrional has successfully support healed the collection. Serial CT renal protocol showed a healed retroperitoneal collection and patient made a good clinical recovery. PCNL has promising stone clearance rate. However, it carries complications. A rare yet important complication; colonic perforation is a serious complication that if detected earlier, good clinical recovery can be achieved conservatively